2021
DOI: 10.1298/ptr.e10064
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic Pulsed Current Stimulation of Duty Cycle 10% Promotes Differentiation of Human Dermal Fibroblasts into Myofibroblasts

Abstract: Objective: Many clinical trials have shown the therapeutic effects of electrical stimulation (ES) in various conditions. Our previous studies showed that ES (200 μA and 2 Hz) promotes migration and proliferation of human dermal fibroblasts (HDFs). However, the effective duty cycle and the effect of ES on myofibroblast differentiation are unclear. This study aimed to investigate the relationship between duty cycle and myofibroblast differentiation. Methods: HDFs were subjected to ES (200 μA and 2 Hz) for 24 h w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…34,35) In addition, the proliferation of myofibroblasts by electrical stimulation 36) is also considered to have affected the contraction of the undermining. Uemura et al 37) reported that for in vitro cell cultures using fibroblasts, a stimulation intensity of 200 µA, frequency of 2 Hz, and DF of 10% promoted differentiation into myofibroblasts and contraction of collagen gel. However, these were in vivo or in vitro studies; thus, it is unclear whether there was a di-rect effect, although it cannot be denied that MPMC therapy exerted a beneficial effect on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…34,35) In addition, the proliferation of myofibroblasts by electrical stimulation 36) is also considered to have affected the contraction of the undermining. Uemura et al 37) reported that for in vitro cell cultures using fibroblasts, a stimulation intensity of 200 µA, frequency of 2 Hz, and DF of 10% promoted differentiation into myofibroblasts and contraction of collagen gel. However, these were in vivo or in vitro studies; thus, it is unclear whether there was a di-rect effect, although it cannot be denied that MPMC therapy exerted a beneficial effect on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that the degree of cell proliferation changes when the ES duty ratio differs (Yoshikawa Y et al 2016). Reports also suggest that the duty ratio affects myo broblast differentiation (Uemura M et al 2021). Thus, there are several electrical condition parameters, and the cellular response may vary greatly.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation can have diverse effects on cells, such as facilitating myofibroblast differentiation for wound healing [ 34 , 35 , 36 ] or increasing cell proliferation and altering ECM components [ 20 , 36 , 37 ]. The different outcomes can be attributed to several factors, such as differences in the cell types studied and the current form.…”
Section: Discussionmentioning
confidence: 99%